ELABORATION OF NEW METHODS FOR DECONTAMINATION OF FISH AND FISH PRODUCTS FROM METACERCARIAE OF Opisthorchis felineus Rivolta, 1884 - A. N. Pelgunov (Российский паразитологический журнал, 2016)
Objective of research: elaboration of effective and energy-efficiency methods for the decontamination of fishes of the larvae of Opisthorchis both in industrial and domestic environment.  Materials and methods:  In  the experiment we  used orfes  (nerflings)  spontaneously infected with Opisthorchis felineus  metacercariae.  Vacuum treatment, electrodynamic shock vibration,  ultrasonic irradiation, and microwave radiation were used for treatment of fish infected with opisthorchids.  O. felineus metacercariae were identified by artificial digestion method. The viability of metacercariae was determined according to  the  preservation of morphological structure of  metacercariae, their mobility, excystation of larvae using the trypsin-bile salt excystation method (experimental infestation of golden hamster and white outbreed mice).  Results and discussion:   In was determined  that O. felineus metacercariae are resistant to vacuum, electrodynamic shock vibration and ultrasound mostly due to the structure of their capsule. Even when using the microwave we can observe  the total decontamination of fish  of Opisthorchis metacercariae.